Lead poisoning and cystatin-C in children - Yuri Yuri; Praisilia Riani Najoan; Stefanus Gunawan; Adrian Umboh (Paediatrica Indonesiana, 2015)
Background Lead pollution is a global problem both in developed and developing countries. Lead poisoning is associated with decreased glomerular filtration rate (GFR) and is a risk factor for acute kidney injury (AKI). Serum cystatin-C is a more precise test of GFR than serum creatinine level, as serum cystatin-C levels rise earlier than serum creatinine, when GFR decreases. Objective To assess for a possible correlation between lead poisoning and cystatin-C levels in children. Methods We conducted a cross-sectional study in children aged 6-11 years with a history of lead poisoning from elementary schools in Talawaan District, North Minahasa Regency from July to October 2013. Cystatin-C and blood lead levels (BLL) were measured in all subjects. Spearman’s rho test was used to analyze a potential correlation between BLL and cystatin-C level. Results This study included 41 children, comprising 21 boys and 20 girls. Their median age was 8.50 (range 6.8-10.7) years. Elevated levels of cystatin-C did not exceed normal values, however, we found a positive correlation between BLL and cystatin C (r=0.419, P=0.006). Conclusion There is a positive correlation between BLL and cystatin C level in children with lead poisoning. Regular monitoring of BLL, medical intervention, and an epidemiological study to help find the sources of contamination are needed for children with lead poisoning.